Durability of Response to Primary Chemoablation of Low-Grade Upper Tract Urothelial Carcinoma Using UGN-101, a Mitomycin-Containing Reverse Thermal Gel: OLYMPUS Trial Final Report. Issue 4 (17th April 2022) - Matin, Surena F.; Pierorazio, Phillip M.; Kleinmann, Nir; Gore, John L.; Shabsigh, Ahmad; Hu, Brian; Chamie, Karim; Godoy, Guilherme; Hubosky, Scott G.; Rivera, Marcelino; O'Donnell, Michael; Quek, Marcus; et al.
Abstract : Abstract : Purpose: Our goal was to evaluate long-term safety and durability of response to UGN-101, a mitomycin-containing reverse thermal gel, as primary chemoablative treatment for low-grade upper tract urothelial carcinoma. Materials and Methods: In this open-label, single-arm, multicenter, phase 3 trial (NCT02793128), patients ≥18 years of age with primary or recurrent biopsy-proven low-grade upper tract urothelial carcinoma received 6 once-weekly instillations of UGN-101 via retrograde catheter to the renal pelvis and calyces. Those with complete response (defined as negative ureteroscopic evaluation, negative cytology and negative for-cause biopsy) 4–6 weeks after the last instillation were eligible for up to 11 monthly maintenance instillations and were followed for ≥12 months with quarterly evaluation of response durability. Durability of complete response was determined by ureteroscopic evaluation; duration of response was estimated by the Kaplan-Meier method. Treatment-emergent adverse events (TEAEs) were monitored. Results: Of 71 patients who initiated treatment, 41 (58%) had complete response to induction therapy and consented to long-term followup; 23/41 patients (56%) remained in complete response after 12 months (95% CI 40, 72), comprising 6/12 (50%) who did not receive any maintenance instillations and 17/29 (59%) who received ≥1 maintenance instillation. Kaplan-Meier analysis of durability was estimated as 82% (95% CI 66, 91) at 12 months. Ureteric stenosis was the most frequently reported TEAE (31/71, 44%); an increasing number of instillations appeared to be associated with increased incidence of urinary TEAEs. Conclusions: Durability of response to UGN-101 with or without maintenance treatment is clinically meaningful, offering a kidney-sparing therapeutic alternative for patients with low-grade disease.